Penerapan Konvergensi Media Radio Gema Wana Prima 98.6 FM Sangatta di Era Digitalisasi - Taufik Hidayat; Silviana Purwanti; Johantan Alfando WS; Donny Kristian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The advancement of communication technology has created new challenges for traditional media, including radio. This study aims to analyze the implementation of media convergence by Gema Wana Prima (GWP) 98.6 FM, a local radio station in Sangatta, East Kalimantan, in adapting to the digital era. This research uses a descriptive qualitative method through in-depth interviews, participatory observation, and documentation. The results show that GWP has adopted several elements of Rich Gordon’s media convergence theory, particularly Tactical Convergence, structural Convergence, and storytelling convergence. The station actively utilizes social media and digital platforms, although ownership and Information gathering convergence have not been fully implemented due to limited resources. This study concludes that local media can independently adopt selective convergence strategies to maintain relevance amid media landscape changes.